Avaliação da aplicabilidade do custeio baseado em atividades: um estudo comparativo em hospitais filantrópicos do município de São Paulo - Cardoso Neto, José Olímpio (2012)
This dissertation presents the results of a descriptive study on the applicability of activity-based costing (ABC) in philanthropic hospitals in São Paulo. Initially, the study is produced from literature searches, constituting the foundation of the theoretical underpinning of the work. Aiming at increasing the information about the time visits were made in a philantropic hospital, seeking to understand the shape and importance of monitoring hospital costs experienced in daytoday these hospitals. In this intermediate phase interviews were conducted with hospital managers, facing the daily production of the hospitals. These steps were critical to completing the questionnaire to be applied in the research. We selected three hospital organizations outside the target population to achieve the pre-test. To achieve the objective of the study was a questionnaire, with almost dichotomous questions (closed) and multiple choice. The results revealed that the majority of the sample does not use the activitybased costing, and the determining factor for not using this methodology the understanding that: the current costing system meets the organization, followed by cost / benefit profile for use , and the high complexity of applying the ABC. However, in some organizations is being studied to apply this methodology. Considering also the results obtained in the research, there is an organization that applied the concepts of the methodology throughout the hospital, having deployed the ABC over a period exceeding three years, and currently uses a methodology that maps the time and resources involved in the processes without entering the mapping of all the activities themselves